Respuestas

2012-10-23T06:47:05+02:00

(8uv3 -12u2v2  +4u3v)(-3u2v2  +5u3v -9u)=

(8uv3 - 12u2v2 + 4u3v) (-3u2 +5u3v -9u) =

-24u3v3 + 40u4v4 – 72uv – 60u5v3- 96u8v3 + 20u6v2 – 36u4v

(8uv3)(-3u2) + (8uv3) (5u3v) + (8uv3)(-9u) =          

-24 u3v3 + 40u4v4   - 72u3v3


(-12u2v2)(-3u2) + (-12u2v2) (5u3v) + (-12u2v2) (-9u) =                      

36u4v4 – 60u5v3 + 108u3v2 


(4u3v)(-3u2) + (4u3v) (5u3v) + (4u3v)(-9u) =                        

 -12u5v + 20u6v2 –36u4v


-24u3v3 + 40u4v4 -   72uv   - 60u5v3 –   96u8v3 + 20u6v2 – 36u4v

2012-10-23T07:04:25+02:00

2/3 a4bc3 + 4ab3c2 = abc2(2/3 a3c + 4b2)

(VmWn + 4)(VmMn – 2/6) = (VmWn)2 - 2/6(VmWn) + 4(VmMn) - 4/3

                                      = (VmWn)2 + 11/3 (VmWn) - 4/3

(8uv3 - 12u2v2 + 4u3v)(-3u2 +5u3v -9u) = -24u3v3 + 40u2v4 - 72u2v3 + 36u4v2 - 60u5v3 + 108u3v2 - 12u5v + 20u6v2 - 36u4v = 4u2v (-6uv2 + 10v3 - 18v2 + 9u2v - 15u3v4 + 27uv - 3u3 + 5u4v - 9u2)